2019
DOI: 10.1111/febs.15144
|View full text |Cite
|
Sign up to set email alerts
|

The active nuclear form of SREBP1 amplifies ER stress and autophagy via regulation of PERK

Abstract: Endoplasmic reticulum (ER) stress and autophagy dysfunction contribute to the establishment and progression of diverse pathologies. Proteolytic activation of the transcription factor nSREBP1 is induced under ER stress; however, little is known about how SREBP1 and its nuclear active form nSREBP1 influence autophagy and unfolded protein response (UPR) activation in osteosarcoma cells. Our research focused on the effect of SREBP1/nSREBP1 upon apoptosis and autophagy during ER stress and the molecular mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Our results imply that the Simva–TMZ-mediated inhibition of autophagy flux and (subsequent) induction of cell death is connected to the PERK pathway in U87 cells but not in U251 cells. Recently, it has been shown that apoptosis and autophagy induced by sterol regulatory element-binding proteins are related to PERK and UPR in osteosarcoma cells [ 70 ]. Therefore, it is possible that in U87 cells, Simva–TMZ-induced cell death is regulated via autophagy and UPR and connected to sterol regulatory element-binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Our results imply that the Simva–TMZ-mediated inhibition of autophagy flux and (subsequent) induction of cell death is connected to the PERK pathway in U87 cells but not in U251 cells. Recently, it has been shown that apoptosis and autophagy induced by sterol regulatory element-binding proteins are related to PERK and UPR in osteosarcoma cells [ 70 ]. Therefore, it is possible that in U87 cells, Simva–TMZ-induced cell death is regulated via autophagy and UPR and connected to sterol regulatory element-binding proteins.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most well-established transcription factors affecting FASN is SREBP; SREBP1 promotes fatty acid synthesis, while SREBP2 is more specific to cholesterol synthesis [ 33 ]. SREBP1 amplifies autophagy [ 34 ] that can regulate the hepatocellular lipid accumulation by its selective degradation. Accordingly, increased ALOX15 expression levels in animals fed WQ and Ch may suggest that mediators such as lipoxin, resolvin, and protectin, among other metabolites, could contribute to ameliorate hepatic inflammation and insulin resistance [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…(69) MGAT1 and MGAT2 are mostly active in rodents and humans, while MGAT3 is active in humans. (70) Mice fed an HFD gained high levels of MGAT1, (71) and MGAT1 knockout reduced the TAG content in the liver of mice fed a 40% highfat/fructose and cholesterol diet. (72) In addition, the inhibitor of MGAT2 has been reported to have the capacity of preventing hepatic steatosis.…”
Section: Mgatmentioning
confidence: 99%